Factors associated with shorter time to death and causes of mortality among deceased patients with systemic sclerosis: a multicentre retrospective study - Balci, M. A.; Yagbasan, Z.; Gunduz, I; Bayindir Akbas, A. N.; Albayrak, F.; Zengin, O.; Yildirim-Cetin, G. (Taylor & Francis Ltd, 2026)
Objective To describe causes of death and identify clinical factors associated with shorter time to death among deceased patients with systemic sclerosis (SSc) in Turkey.Method This retrospective multicentre study screened hospital databases across 19 tertiary rheumatology centres between 2004 and 2024 for deceased patients aged >= 16 years with ICD-10 codes beginning with M34. Eligibility was confirmed according to the 2013 American College of Rheumatology/European Alliance of Associations for Rheumatology classification criteria; 266 of 294 identified patients were included. Dates of death were verified through the national death registry. Baseline clinical features, organ involvement, and key echocardiographic measures were extracted from medical records. Time to death was defined as the interval from diagnosis to death. Cause-specific Cox regression models were constructed for SSc-related and non-SSc-related deaths.Results Of 266 deaths, 122 (45.9%) were SSc related and 144 (54.1%) non-SSc related. Among SSc-related deaths, interstitial lung disease (ILD) (50.0%, n = 61) and pulmonary arterial hypertension (PAH) (42.6%, n = 52) predominated. Among non-SSc-related deaths, cardiovascular causes (38.9%, n = 56), infections (33.3%, n = 48), and malignancy (19.4%, n = 28) were most frequent. In multivariable models, older age at diagnosis, scleroderma renal crisis, palpitations, ILD, and higher echocardiographic pulmonary artery systolic pressure were independently associated with shorter time to SSc-related death, whereas older age at diagnosis and malignancy were associated with shorter time to non-SSc-related death.Conclusion Pulmonary complications predominated among SSc-related deaths, whereas cardiovascular disease, infections, and malignancy were the leading contributors to non-SSc-related mortality. These findings support systematic cardiopulmonary assessment and comorbidity management.
Keywords: Survival